PLANNING DEVELOPMENT TOURISM IN ISLAMIC PERSPECTIVES AT LAKE TOBA REGION - M.R. Khairul Muluk; Abdullah Said; Siti Hajar; Bambang Supriyono (Journal of Islamic, Social, Economics and Development, 2019)
Tourism development have contribution a very significant in national economic development, if in the development carried out in accordance with good planning. Tourism is very important in increasing human resources related to understanding and mastering science and technology that will add insight and provide optimal enlightenment to the community. Thus, tourism development planning is needed to have religious nuances, for example tourism in an Islamic perspective. Because in the religious element that tourism can create good and bad, then in accordance with the view of religion will be positive if tourism development planning is run in a good way to achieve good goals. The purpose of this study is to find out how tourism development planning is in the perspective of Islam in the Lake Toba Region. The method used in this study is a qualitative method with SWOT analysis, so that it can show strengths, opportunities, threats and weaknesses in tourism development planning in the perspective of Islam in the Lake Toba Region.